Bribing the Self - Uri Gneezy; Silvia Saccardo; Marta Serra-Garcia; Roel van Veldhuizen (Games and Economic Behavior, 2020)
Expert advice is often biased in ways that benefit the advisor. We demonstrate how self-deception helps advisors be biased while preserving their self-image as ethical and identify limits to advisors' ability to self-deceive. In experiments where advisors recommend one of two investments to a client and receive a commission that depends on their recommendation, we vary the timing at which advisors learn about their own incentives. When advisors learn about their incentives before evaluating the available investments, they are more likely to be biased than when they learn about their incentives only after privately evaluating the investments. Consistent with self-deception, learning about the incentive before evaluating the options affects advisors' beliefs and preferences over the investments. Biased advice persists with minimal justifications but is eliminated when all justifications are removed. These findings show how self-deception can be constrained to improve advice provision.
Keywords: D03; D83; C91; 300; advice; self-deception; self-image; motivated beliefs; laboratory experiment